Analysis of precipitation and convection in the west Pacific during the PISTON field campaign - Chudler, Kyle, author; Rutledge, Steven, advisor; Bell, Michael, committee member; Maloney, Eric, committee member; Reising, Steven, committee member (Colorado State University. Libraries, 2022)
Tropical convection is a meteorological phenomenon with important impacts on the atmosphere, both locally and globally. Consequently, it has been an intensely studied topic for many years. Importantly, several ship-based field campaigns have taken place over tropical oceans. Such field campaigns are vital to the advancement of knowledge in this field, as meteorological observations over these open oceans are otherwise scant or non-existent. The latest project to examine tropical convection is the Propagation of Intraseasonal Oscillations (PISTON) field campaign, which took place in the western North Pacific in the late-summer and early-fall of 2018 and 2019. On board the PISTON ships was the SEA-POL weather radar, the first polarimetric weather radar designed specifically for deployment at sea. In addition to taking traditional radar measurements of precipitation intensity and velocity, SEA-POL's polarimetric measurements also provide insights into the size, shape, and composition of hydrometeors within precipitating systems. By combining SEA-POL's unique measurements with other meteorological datasets, this work presented in this dissertation provides new insights in tropical convection in the Pacific warm pool. Chapter 2 of this dissertation provides an overview of the variability in convection observed during the PISTON cruises, and relates this variability to large-scale atmospheric conditions. Using an objective classification algorithm, precipitation features are identified and labeled by their size (isolated, sub-MCS, MCS) and degree of convective organization (nonlinear, linear). It is shown that although large mesoscale convective systems (MCSs) occurred infrequently (present in 13% of radar scans), they contributed a disproportionately large portion (56%) of the total rain volume. Conversely, small isolated features were present in 91% of scans, yet these features contributed just 11% of the total rain volume, with the bulk of the rainfall owing to warm rain production. Convective rain rates and 30-dBZ echo-top heights increased with feature size and degree of organization. MCSs occurred more frequently in periods of low-level southwesterly winds, and when low-level wind shear was enhanced. By compositing radar and sounding data by phases of easterly waves (of which there were several in 2018), troughs are shown to be associated with increased precipitation and a higher relative frequency of MCS feature occurrence, while ridges are shown to be associated with decreased precipitation and a higher relative frequency of isolated convective features. During PISTON, SEA-POL routinely measured extreme values of differential reflectivity in the cores of small, isolated convection, owing to the presence of large drops. Chapter 3 examines the structure and frequency of cells containing large drops. Cells with high differential reflectivity (> 3.5 dB) were present in 24% of all radar scans. The cells were typically small (8 km2 mean area), short lived (usually < 10 minutes), and shallow (3.7 km mean height). High differential reflectivity was more often found on the upwind side of these cells, suggesting a size sorting mechanism which establishes a low concentration of large drops on the upwind side. Differential reflectivity also tended to increase at lower altitudes, which is hypothesized to be due to continued drop growth, increasing temperature (dielectric effect), and evaporation of smaller drops. Rapid vertical cross section radar scans, as well as transects made by a Learjet aircraft with on-board particle probes, are also used to analyze these cells, and support the conclusions drawn from statistical analysis. In Chapter 4, the observations of precipitation from spaceborne Ku-Band precipitation radar (KuPR) from the Global Precipitation Mission Dual-Frequency Precipitation Radar is compared surface observations from SEA-POL. Over the 18 instances where KuPR and SEA-POL made concurrent measurements of precipitation, the average rain rate in KuPR was 50% lower than in SEA-POL, but the raining area was 113% higher. The net effect of these two differences of opposite sign was for KUPR to have 23% more rain volume than SEA-POL. The limited resolution of KuPR (5x5 km) causes it to underestimate rain rate in small convective cores, but also over-broaden raining features beyond their true extent. It is also shown that KuPR tends to slightly overestimate rain rate below the melting layer in stratiform rain, likely due to overcorrection of attenuation below radar bright bands. Using a statistical model to simulate KuPR rain volume, it was found that KuPR would theoretically overestimate rain volume during trough phases of the easterly waves observed during PISTON (when there was more precipitating area), and underestimate rainfall during ridge phases (when there was less precipitating area).